ASAS KEADILAN DALAM SUPLAI MAKAN TAHANAN KEPOLISIAN DAN LEMBAGA PEMASYARAKATAN DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 - danang wijayanto; Martin Roestamy; endeh Suhartini (JURNAL ILMIAH LIVING LAW, 2020)
This study aims to find out and analyze the mechanism of procurement of food supplies, and the achievement of justice for prisoners of the Police and Penitentiary. The research method used in this study is normative juridical research. The results of this study are: 1) The mechanism of procurement of prisoner food supplies Police and Penitentiary, has sought to fulfill the right of prisoners to food in accordance with applicable standards and also Minister of Law and Human Rights regulations Number M.HH-01.PK.07.02 of 2009. This can be seen from timely food supply and is served three times a day by the Police and Penitentiary even though the menu presented is less varied when viewed from nutritional adequacy figures due to budget constraints, 2) Procurement of goods and services in the field of eating food of police and Penitentiary detainees to achieve justice, the authority of the Budget User Authority (KPA) during the process of auctioning prisoner food ingredients. So based on its authority, KPA has used its authority during the process of auctioning prisoner food ingredients, the legal arrangements for delays in obtaining prisoner food suppliers in the following fiscal year have no clear legal instruments so KPA has taken its own initiative in procuring prisoner food ingredients.